Artificial intelligence (AI) as English learning tools: Perceived impacts on students’ motivation and confidence - Alifarga Kresnayoga Susanto; Bambang Yudi Cahyono (University of Muhammadiyah Malang, 2026)
The development of Artificial Intelligence (AI) has influenced the landscape of English language learning, including in higher education. This study aims to identify the types of AI tools used by English Language Education (ELE) students and analyze their perceived impacts on students’ motivation and confidence in learning English. The research method used is a mixed method, combining a quantitative and qualitative approach through questionnaires and semi-structured interviews. A total of 40 undergraduate ELE students participated in filling out the questionnaires, and nine of them participated in the interviews. The quantitative data were analyzed using descriptive statistics, while qualitative data were analyzed through thematic analysis. The results of the study indicated that the students actively used various AI tools, including ChatGPT, Grammarly, Quillbot, DeepL, and Perplexity AI to support their English learning. The majority of students had a positive perception on the use of AI. They believe that AI tools increased their motivation and confidence. The learning process is more dynamic, flexible, and enjoyable learning experiences. Nevertheless, some students raised concerns about the risk of dependency on AI, highlighting the importance of critical thinking and teachers’ direction. Therefore, it is essential for teachers to maintain a balance between integrating AI into the teaching and learning process and improving students' digital literacy and reflexive awareness. Finally, this study emphasizes the potential use of AI in English language learning increases students’ motivation and confidence, making it a useful tool for adaptive and autonomous learning in the digital age